Perpustakaan Umum di Kota Panyabungan dengan Pendekatan Arsitektur Neo Vernakular - Sulaiman, Ahmad; Maulana , Sherlly (JAUR (JOURNAL OF ARCHITECTURE AND URBANISM RESEARCH), 2025)
The design of this Public Library is motivated by the lack of public library facilities in the Mandailing Natal Regency, particularly in the Panyabungan District and its surroundings. Despite being an area experiencing growth in education and the economy, there is a significant need for a library in this region for the benefit of the community, students, and scholars. This final project aims to address this issue by proposing the design of a one-phase public library in the Panyabungan District of the Mandailing Natal Regency. The design methodology employed for this project is the neo-vernacular architectural approach. The chosen design location was determined through surveys and personal data analysis to support the planning of the Mandailing Natal Regency Public Library in the city of Panyabungan. In this design, the extensive work on the Mandailing Natal public library is guided by the transformation of traditional Mandailing houses. Given the uniformity of the surrounding buildings, the goal is to create an attractive structure that can become an iconic landmark within the environment. Neo-vernacular architecture is a design approach that prioritizes environmental considerations.